MICROSSIMULAÇÃO PARA ANÁLISE DE ROTATÓRIAS: UM ESTUDO BIBLIOMÉTRICO: MICROSIMULATION FOR ROUNDABOUTS ANALYSIS: A BIBLIOMETRIC STUDY - Porto, Ana Beatriz de Britto; de Abreu, Victor Hugo Souza (Brazilian Journal of Production Engineering, 2020)
Traffic microsimulation has become an important strategy for verifying road improvement proposals because it makes it possible to represent or model the behavior of traffic and the interactions of the elements of a system to provide a prior assessment of its performance. Regarding roundabout analysis, this reality is no different. Many studies use traffic microsimulators to evaluate the deployment of new roundabouts as well as to suggest proposals for improvements to existing ones. Thus, this article seeks, through a bibliometric review, to collect and gather studies that use microsimulators to analyze the performance of roundabouts. The results indicate that the subject is still expanding, that VISSIM stands out as the main microsimulator and that these studies can be divided into 8 major application areas.